Two new species of amphipod genus Stenothoe Dana, 1852 (Stenothoidae) associated with fouling assemblages from Nhatrang Bay, Vietnam - Marin, Ivan; Sinelnikov, Sergey (Zootaxa, 2018)
Two new species of amphipod genus Stenothoe Dana, 1852 (Crustacea, Amphipoda, Stenothoidae) are described from hydroids collected in fouling communities of floating aquaculture platforms in Nhatrang Bay (Vietnam) representing the first record of the genus from coastal waters of Vietnam. The new species can be clearly separated from congeners by the structure of the mandible, maxilla II, the shape of gnathopod II, the armature of uropod III and the telson. The discussion is presented in the paper.